Research Trends and Foci in Osteoarthritis Pain from 2012 to 2022: Bibliometric and Visualization Study - Zhao C; Yang G; Ji B; Jin H; Naranmandakh S; Li Y (Journal of Pain Research, 2023)
Changtai Zhao,1,* Guang Yang,2,* Bingzhou Ji,2 Hongfu Jin,2 Shinen Naranmandakh,3 Yusheng Li2,4 1Xiangya School of Medicine, Central South University, Changsha, Hunan, 410008, People’s Republic of China; 2Department of Orthopedics, Xiangya Hospital, Central South University, Changsha, Hunan, 410008, People’s Republic of China; 3Department of Chemistry, School of Arts and Sciences, National University of Mongolia, Ulaanbaatar, 14201, Mongolia; 4National Clinical Research Center for Geriatric Disorders, Xiangya Hospital, Central South University, Changsha, Hunan, 410008, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yusheng Li; Shinen Naranmandakh, Email liyusheng@csu.edu.cn; smandakh@num.edu.mnBackground: Osteoarthritis (OA) is a painful and complex joint disease. The unique mechanisms and potential interventions of OA-induced pain have attracted researchers’ attention in recent years. Bibliometric and visualization analysis is a comprehensive scientific method that integrates mathematical and statistical approaches to explore research priorities in a specific field. However, there are few studies on OA pain using bibliometric analysis.Purpose: This study aimed to explore research trends and hotspots in OA pain research field, offer practical guidance to researchers looking for top-notch scholars/institutions/countries, and provide suggestions for journal submissions by analyzing the existing literature.Methods: Raw data were extracted from Web of Science Core Collection. Microsoft Excel, the R package “bibliometrix”, VOSviewer and CiteSpace software were used to analyze data and visualize relevant results.Results: A total of 2493 articles were included for further bibliometric and visualization analysis. During the investigated period, 2021 with 343 publications was the most productive year. Fillingim, Roger B. and Bennell, Kim L. with 32 articles were the most productive authors. Most publications were from the USA (797 articles, 20,727 citations). Rehabilitation and treatment of OA pain were the hotspots in OA pain research area. The top-contributing journal was Osteoarthritis and Cartilage. Boston University (91 articles; 4050 citations) was the most active institution.Conclusion: The total publications of OA pain generally increasing over the time in the last decade, and the escalating rate remained a high level. This is the first comprehensive bibliometric study in OA pain research field, and it will offer practical guidance to researchers in this field.Graphical Abstract: Keywords: osteoarthritis pain, bibliometric analysis, research trends, VOSviewer, CiteSpace